Isolation and structure elucidation of natural products of three soft corals and a sponge from the coast of Madagascar. Issue 12 (7th March 2017) - Rahelivao, Marie Pascaline; Lübken, Tilo; Gruner, Margit; Kataeva, Olga; Ralambondrahety, Rahanira; Andriamanantoanina, Hanta; Checinski, Marek P.; Bauer, Ingmar; Knölker, Hans-Joachim
Abstract : The Madagascan soft coral Capnella fungiformis provided the two diastereoisomeric ethyl furancarboxylates1 and2 and the diepoxyguaiane sesquiterpene oxyfungiformin (3 ). Abstract : We investigated the three soft corals Sarcophyton stellatum, Capnella fungiformis and Lobophytum crassum and the sponge Pseudoceratina arabica, which have been collected at the coast of Madagascar. In addition to previously known marine natural products, S. stellatum provided the new (+)-enantiomer of the cembranoid (1 E, 3 E, 11 E )-7, 8-epoxycembra-1, 3, 11, 15-tetraene (2 ). Capnella fungiformis afforded three new natural products, ethyl 5-[(1 E, 5 Z )-2, 6-dimethylocta-1, 5, 7-trienyl]furan-3-carboxylate (6 ), ethyl 5-[(1 E, 5 E )-2, 6-dimethylocta-1, 5, 7-trienyl]furan-3-carboxylate (7 ) and the diepoxyguaiane sesquiterpene oxyfungiformin (9a ). The extracts of all three soft corals exhibited moderate activities against the malarial parasite Plasmodium falciparum . Extracts of the sponge Pseudoceratina arabica proved to be very active against a series of Gram-positive and Gram-negative bacteria.